Modeling of Cracking of the Concrete Cover Taking into Account the Coupled Diffusion/Mechanical Process - Yurkova, Kseniya; Krykowski, Tomasz (Computer Assisted Methods in Engineering and Science, 2023)
This paper presents a mechanical-diffusion one-way coupled corrosion model that allows the analysis of both accelerated and natural reinforcement corrosion. The impact of corrosion products on the concrete cover is exerted using the tensor of the volumetric strain rate dependent on the rate of concentration change of corrosion products or the rate of concentration change of ferrous ions. The approach proposed in the paper enables the analysis of the impact of corrosion products with a complex composition that depends on the intensity and density of the electric current. The model also enables the analysis of cases where the distribution of corrosion products is inhomogeneous around the circumference of the rebar.